Know You Mind Manage Your Emotions: Practical Psychology Training for a Lighter Life - Jihan Luthfi Nabillah; Indah Rosdiyan; Leo Permana; Jusini Delas Halifah; Arfian Arfian (Inovan Publisher, 2025)
The training program, “Recognize Your Thoughts, Manage Your Emotions: Practical Psychology for a Lighter Life,” is designed to help students recognize negative thought patterns and manage their emotions in a healthier way amid academic pressures. The training was held at Bhayangkara University Jakarta Raya, involving 30 students from various majors. The training material covers four main components: cognitive distortions, self-talk, emotion regulation, and emotion validation, delivered through an experiential learning approach in the form of discussions, breathing exercises, journaling, role-playing, and reflection. Evaluation was conducted using pre-tests and post-tests with paired sample t-test analysis. The results showed a statistically significant increase (t(29) = -5.213, p < .001) with a large effect size (Cohen’s d = -0.952), indicating that the training had a strong impact on enhancing participants’ psychological awareness and skills. Despite challenges such as participant tardiness and training time not fully aligning with the schedule, the training proceeded in accordance with learning objectives. Activity documentation was conducted in the form of photos and videos. In conclusion, this training is effective as a promotional and preventive measure for student mental health and can be replicated on a larger scale in higher education settings.